2021
DOI: 10.1101/2021.11.16.468598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lonely in the dark: trauma memory and sex-specific dysregulation of amygdala reactivity to fear signals

Abstract: Loneliness exacerbates psychological distress and increases the risk of psychopathology after trauma exposure. The prevalence of trauma-associated disorders varies substantially between sexes, and accumulating evidence indicates sex-specific effects of loneliness. However, it is still unclear whether a lack of social connectedness affects trauma-induced intrusions and the neural processing of fear signals. Moreover, it is uncertain, whether loneliness plays a different role in women and men. We used a prestrat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…This adds to numerous studies revealing female gender as a risk factor for loneliness 77 , 78 . Interestingly, however, recent neuroimaging studies indicate that loneliness-associated neural effects may be more pronounced in high lonely men than women 79 , 80 .…”
Section: Discussionmentioning
confidence: 99%
“…This adds to numerous studies revealing female gender as a risk factor for loneliness 77 , 78 . Interestingly, however, recent neuroimaging studies indicate that loneliness-associated neural effects may be more pronounced in high lonely men than women 79 , 80 .…”
Section: Discussionmentioning
confidence: 99%
“…This adds to numerous studies revealing female gender as risk factor for loneliness 76,77 . Interestingly, however, recent neuroimaging studies indicate that loneliness-associated neural effects may be more pronounced in high lonely men than women 78,79 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a recent study found that loneliness may influence trauma memory in a sex-dependent manner. Specifically, lonely men, but not lonely women, exhibited more intrusive thoughts after experimental trauma and this phenotype was related to amygdala hyperreactivity during both fear conditioning and habituation processes, suggesting that the limbic system is a potential target for interventions that increase social connectedness [55].…”
Section: Memory and Working Memorymentioning
confidence: 96%
“…Furthermore, patients with substance abuse [46][47][48], borderline personality disorder [49,50], and schizoid personality disorder [51] report more loneliness and social disconnection than healthy controls. In addition, loneliness is a potential risk factor for post-traumatic stress disorder [52,53] and enhances intrusive thoughts after trauma exposure [54,55]. Overall, loneliness and social isolation are critical risk factors for several somatic and mental disorders and thus should be considered in therapeutic protocols.…”
Section: Detrimental Health Consequences Of Lonelinessmentioning
confidence: 99%